Prímá osteosyntéza dentu--multicentrická studie - Stulík, J; Suchomel, P; Lukás, R; Chrobok, J; Klézl, Z; Taller, S; Krbec, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2002)
PURPOSE OF THE STUDY: Direct osteosynthesis is a method of choice for the treatment of odontoid process fractures. It is based on insertion, from the anterior approach, of one or two screws from the C2 body into the apex of the odontoid across the fracture line. The tensile action of screws results in compression of fragments and stabilization of the fracture. The aim of the study was to evaluate a group of patients treated by this method and to compare our results with those reported in the foreign literature. MATERIAL: A total of 99 patients were treated by direct osteosynthesis of the odontoid in the departments involved in the study between 1994 and 2001. METHODS: Patients indicated for this surgery were those with fractures of type II according to Anderson and D'Alonzo and those with type III fractures but only when the fracture line went across the articulation surfaces of C1-C2, when closed reduction was not possible or the patients were not indicated for halo fixation. Direct osteosynthesis was not applied to fractures with comminution at the base of the odontoid, irreducible fractures, odontoid fractures combined with dislocated fractures of the atlas or pathological fractures. Severe kyphosis of the cervical spine or a large thoracic cage was also regarded as a contraindication. RESULTS: All the 99 patients were followed up from 3 up to 102 months, with an average of 28.5 months; only in seven patients, the follow-up period was shorter than 6 months. The most frequent subjective complaint was a painful operation wound. This usually resolved within two weeks of surgery. Except for four patients, alle were satisfied with the outcome. Type II fractures were diagnosed in 84 and type III fractures in 15 cases. A total of 174 screws were inserted into the odontoid processes of 99 patients. A single screw was used in 25 and two screws in 73 patients. In one case, three screws had to be inserted. Screw lenght ranged from 36 to 44 mm, diameter was 40.9 mm. Three months after surgery, X-ray examination, both in flexion and extension, did not reveal any instability in any of the patients. No morphological change in the C2-C3 intervertebral space was observed Of 92 (92.9%) paitents under longterm follow-up, 84 (91.3%) showed complete healing of the fracture, three died and five patients eventually developed pseudoarthrosis, which was due to a broken screw in three of them. This condition was treated by dorsal fixation of C1-C2 according to Magerl or by one of the dorsal cerclage techniques. The group was free of any perioperative complications related to the anterior approach or injury to nerve structures by screws. DISCUSSION: The most frequent subjective complaint was a painful operation wound. Treatment of odontoid fractures varies according to the type of injury, bone quality and also practice at each department. Type II injuries are highly unstable and, because of the small fracture surface, their healing ability is much lower than in type III fractures. Previously, most of the patients with odontoid injuries were treated conservatively by immobilization in a plaster cast or a brace or, later, by a halo device. In the long term, however, they showed a high proportion of pseudoarthroses (10 to 100%). Direct osteosynthesis of the odontoid by screws permits the maintenance of rotation of the C1-C2 mobile segment. We followed the scheme of indications used abroad but did not perform osteosynthesis to correct pseudoarthrosis. The number of osteosyntheses healed (91.3%) was also in agreement with the literature data. Earlier, we used two screws for all types of fractures. Recently, we have preferred insertion of a single screw in type II and III fractures in narrow odontoids. In the later, there is no danger of rotational dislocation during screw insertion; to insert one screw from the centre of the C2 base is easy and speeds up the procedure. However, in displaced type II and type II T fractures, two screws are a necessity. Similarly to other authors, we recorded a slight limitation of cervical spine rotation in patients at long-term follow-up, particularly in elderly subjects with advanced osteochondrosis. No complications leading to deterioration of the patient's state were recorded. CONCLUSIONS: Direct osteosynthesis is a method of choice for most of the type II and indicated cases of type III fractures of the odontoid process of the axis. This surgical procedure facilitates restoration of anatomical conditions of the spine and its immediate stability. Consequently, patients can be readily mobilized and rehabilitated.
Keywords: Fracture Fixation, Internal; Humans; lidé středního věku; Spinal Fractures; Female; Aged; Odontoid Process; dospělí; senioři; lidé; fraktury páteře; vnitřní fixace fraktury; dens axis; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; mladiství